Konsultasi Publik Kegiatan Revitalisasi Gedung Cagar Budaya - Nita Marikena; Yuli Setiawannie (Yayasan Literasi Sains Indonesia, 2023)
The Wharen Huis Building is a building protected by Law Number 11 of 2010 and the Mayor of Medan Decree Number 433/28.K/X/2021. As a preservation and protection effort that will create an optimal function while protecting or maintaining the authenticity of the Wharen Huis Building as a Cultural Heritage of Medan City, the Government of Medan City through the Housing, Residential Areas and Spatial Planning Office of Medan City plans to revitalize the Wharen Huis Cultural Heritage Building by not violating the applicable theories and regulations related to historic building conservation efforts. The Wharen Huis Heritage Building Revitalization/Restoration Activity Plan consists of 3 (three) stages of activity, namely the pre-construction stage, the construction stage, and the operational stage. Each stage of these activities is predicted to have an impact on the environment. Based on the Regulation of the Minister of State for the Environment No. 4 of 2021, the Revitalization of the Wharen Huis Cultural Heritage Building must have a Type C Environmental Impact Analysis (AMDAL). Referring to Government Regulation Number 22 of 2021, those in charge of businesses and/or activities in preparing an EIA must go through the stages of public consultation. The results of the public consultation obtained input related to building ownership, transportation circulation and support for the preservation of cultural heritage. Public consultation activities obtained several important issues that became input in public consultation activities, including the following 1. Regarding the revitalization of the Wharen Huis Cultural Heritage Building, the Medan City Government should be able to coordinate or communicate with the building owner in terms of managing the building, 2. In its construction, there will be an impact that the circulation of transportation passing through the building must be disturbed, it should be necessary to place parking bags to the west of the building that still exists and 3. we are very enthusiastic and supportive in revitalizing this building as an example for the public interest and become something different in terms of learning historical buildings in Medan City.